Nonmember Banks and Monetary Control - Starleaf, Dennis R. (Journal of Finance, 1975)
FOR MORE THAN TWENTY YEARS, the Board of Governors of the Federal Reserve System has periodically requested that the Congress pass legislation to require commercial banks which are not members of the Federal Reserve System (FRS) to meet the same reserve requirements which are set by the Board for member banks. This request has been supported by the several commissions and study groups-including the Commission on Money and Credit and the Hunt Commission-which, during the last twenty years or so, have examined the monetary and financial institutions of the U.S. economy. In recent years, the Board has made its request with somewhat more vigor than previously, pointing out that the nonmember bank portion of total commercial bank demand deposits has risen in the postwar period from approximately 14 per cent in 1946 to about 24 per cent in 1973. There are several different facets to the argument for the extension of FRS reserve requirements to nonmember banks, including issues of regulatory equity between member and nonmember banks, ability of the commercial banking system to withstand financial shocks, etc. However, the heart of the argument is that the Federal Reserve authorities need to be able to set reserve requirements on nonmember bank deposits in order to better control the money stock. The purpose of this paper is to present some evidence which is germane to the question of whether or not FRS reserve requirements on nonmember bank deposits are needed for greater precision in money stock control. Specifically, evidence is presented on the impact of nonmember banks upon the precision of Federal Reserve control over the money stock during the 1960's and early 1970's. Section I contains a discussion of the nonmember bank data problem (a problem which severely limited the scope of this study and which makes its findings less trustworthy than they might otherwise have been) and Section II presents the logic of the empirical inquiry. Section III contains the findings of the study, none of which supports the contention that the absence of FRS